ADMINISTRATIVE DISPOSITION AND LEADERSHIP PERFORMANCE OF PUBLIC SCHOOL HEADS - Sancho, Dell (International Journal of Arts, Sciences and Education, 2023)
Although much information was gathered on effective leadership, there is a gap in addressing the leadership performance of school heads in the transition phase, particularly among school heads in Philippine public basic education considering the now normal milieu. Hence, this study ascertained the relationship between the administrative disposition and leadership performance of the school heads. Using the descriptive-correlational design, the researcher conducted the study among 100 school heads of public elementary schools in the Schools Division of Negros Oriental for the School Year 2022-2023. Results of the study revealed that the respondents had very high administrative disposition in terms of effective planning and budgeting, efficient directing and coordination, apposite organizing and staffing, using technology in pedagogy, use of instructional theories, developing school environment, developing productive relationships with others, and appropriate use of assessment data. Moreover, they had an overall outstanding leadership performance. In particular, they were outstanding in strategic leadership, managing school operations and resources, and focusing on teaching and learning. Interestingly, school heads who are doctorate degree holders and who attended seven to nine seminars or training tend to have higher administrative disposition. Although results show that the overall administrative disposition is not significantly related to leadership performance, it is interesting to note that the specific domain using instructional theories is directly related to the overall leadership performance. This connotes that the respondents who apply more instructional theories are more likely to exhibit better leadership performance. Lastly, implications of the study and suggestions were presented to enhance school leadership in the Philippine context.